PENGARUH PENGGUNAAN MEDIA VISUAL TERHADAP KEMAMPUAN SISWA DALAM MENULIS TEKS DESKRIPSI - Amelia Saruran Sinar (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research aims to determine the effect of using visual media on students' ability to write descriptive text in class XI M at SMA Negeri 2 Palu. The research method used is an experimental method with a pretest-posttest control group design. The research sample consisted of two groups, namely the experimental group which used visual media in the learning process and the control group which used conventional methods. Data was collected through a descriptive text writing test before and after treatment. The results showed that there was a significant increase in students' ability to write descriptive text in the experimental class compared to the control class. The use of visual media helps students understand the material more concretely, increases creativity, and makes it easier for them to formulate descriptive ideas. These findings indicate that visual media has an important role in improving the quality of learning, especially in descriptive text writing skills.